2019
DOI: 10.1002/hec.3927
|View full text |Cite
|
Sign up to set email alerts
|

Payment models in primary health care: A driver of the quantity and quality of medical laboratory utilization

Abstract: Physician payment models' incentives regarding many aspects of primary health care are not well understood. We focus on the case of medical laboratory utilization and examine how physicians' laboratory test ordering patterns change following a switch to a blended capitation payment model from one with fee for service enhanced with pay for performance. Also, within blended capitation, we examine differences between traditional staffing and interdisciplinary teams. Using a propensity score weighted fixed‐effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Moreover, the capitation payment model theoretically motivates GPs to serve healthier patients and reduce the scope of services [44]. It has been also estimated that the transition to capitation payment in primary health care leads to an average of 3% fewer laboratory requisitions per patient in the short term [45]. Traditional forms of FFS and capitation remain the most common payment methods for primary care in the EU health systems.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the capitation payment model theoretically motivates GPs to serve healthier patients and reduce the scope of services [44]. It has been also estimated that the transition to capitation payment in primary health care leads to an average of 3% fewer laboratory requisitions per patient in the short term [45]. Traditional forms of FFS and capitation remain the most common payment methods for primary care in the EU health systems.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated the impact of blended capitation on the quantity and the quality of GPs' delivered services. 44 It could also reduce time pressure and job stress through longer consultation, for instance. 45 No association between the use of electronic health records and GPs' job stress was found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated the impact of blended capitation on the quantity and the quality of GPs’ delivered services. 44 It could also reduce time pressure and job stress through longer consultation, for instance. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Although blended payment models for primary care physicians are growing in popularity (OECD, 2016;Paris, Wei, & Devaux, 2010), the blend that will provide the optimal level of medical services remains largely unknown (Peckham & Gousia, 2014;Rudoler et al, 2015). Empirical evidence on physicians' responses to blended payment models is mixed (Campbell et al, 2007;Chami & Sweetman, 2019;Clemens & Gottlieb, 2014;Devlin, Kpelitse, Li, Mehta, & Sarma, 2020;Kralj & Kantarevic, 2013;Li, Hurley, Decicca, & Buckley, 2014;Sarma et al, 2018;Somé et al, 2019;Sutton, Elder, Guthrie, & Watt, 2010).…”
Section: Previous Literaturementioning
confidence: 99%
“…Our model predicts the type of physicians likely to switch from blended FFS to blended capitation, and importantly, provides a structure in which to understand potential ambiguities in the quantity of services delivered to enrolled and nonenrolled patients during regular and after‐hours. This is an important contribution given that the multitasking nature of physician services (Dumont, Fortin, Jacquemet, & Shearer, 2008; Ma, 1994; Ma & Mcguire, 1997; Shearer, Somé, & Fortin, 2018) has yet to be accounted for in research on blended payment models (Chami & Sweetman, 2019; Kralj & Kantarevic, 2013; Zhang & Sweetman, 2018).…”
Section: Introductionmentioning
confidence: 99%